A Survey of faculty members and lecturers approach About teaching evaluation procedure by EDC questionnaire in School of Allied Health Sciences, Tehran University of Medical Sciences - H Dargahi; E Movahedkor; G Shaham (Tehran University of Medical Sciences, 2009)
Background and Aim: Evaluation is a principle function of management which measure organizational goal attainment and eliminate the problems and modify the policies and procedures. Teachers are the most important educational system inputs and are evaluated with more complexity. There are several evaluation procedures for teachers' evaluation. For example, evaluation of teaching process by students. This research is aimed to conduct faculty members and teachers' opinion about teachers evaluation questionnaires form completed by the students in school of Allied Health Sciences, Tehran University of Medical sciences by the Students. Materials and Methods: All the teachers and faculty members were selected to collect their opinions about teaching evaluation form. The data were analyzed by Excel and descriptive statistical method. Result: The research findings showed that most of the faculty members and teachers believed that teachers evaluation questionnaire form is truly designed and conducted. Discussion and Conclusion: Several universities faculty members and teachers don't believe in teachers evaluation by students, however we think that compound evaluation technical is most appropriate for teachers evaluation.